Surgical exposure of an impacted maxillary canine and increasing a band of keratinized gingiva - Vijayalakshmi R; Ramakrishnan T; Nisanth S (Wolters Kluwer Medknow Publications, 2009)
An adequate amount of keratinized gingival tissue that is under proper plaque control, is a fundamental requirement for periodontal health. When the teeth erupt uneventfully in the center of the alveolar ridge, an adequate amount of keratinized tissue will surround the erupted permanent tooth. Labially or buccally erupting teeth show reduced dimensions of the gingiva as abnormal eruption of permanent teeth restricts or eliminates the keratinized tissue between the erupting cusp and the deciduous tooth. A lack of attached gingiva poses a potential risk for gingival recession in labially or buccally erupted teeth due to the possibility of accumulation of plaque and/or traumatic tooth-brushing during subsequent orthodontic treatment. A good understanding between the orthodontist and periodontist along with proper management of periodontal tissues, can prevent these problems. Various surgical techniques can be employed to uncover impacted teeth. This paper discusses the validity of utilizing periodontal surgery to increase a band of keratinized tissue in a case of an impacted canine erupting from the alveolar mucosa.